A submesoscale coherent vortex in the Ligurian Sea: From dynamical barriers to biological implications. Issue 8 (3rd August 2017) - Bosse, Anthony; Testor, Pierre; Mayot, Nicolas; Prieur, Louis; D'Ortenzio, Fabrizio; Mortier, Laurent; Le Goff, Hervé; Gourcuff, Claire; Coppola, Laurent; Lavigne, Héloïse; Raimbault, Patrick
Abstract: In June 2013, a glider equipped with oxygen and fluorescence sensors has been used to extensively sample an anticyclonic Submesoscale Coherent Vortex (SCV) in the Ligurian Sea (NW Mediterranean Sea). Those measurements are complemented by full‐depth CTD casts (T, S, and oxygen) and water samples documenting nutrients and phytoplankton pigments within the SCV and outside. The SCV has a very homogeneous core of oxygenated waters between 300 and 1200 m formed 4.5 months earlier during the winter deep convection event. It has a strong dynamical signature with peak velocities at 700 m depth of 13.9 cm s −1 in cyclogeostrophic balance. The eddy has a small radius of 6.2 km corresponding to high Rossby number of −0.45. The vorticity at the eddy center reaches − 0.8 f . Cross‐stream isopycnic diffusion of tracers between the eddy core and the surroundings is found to be very limited due to dynamical barriers set by the SCV associated with a diffusivity coefficient of about 0.2 m 2 s −1 . The deep core is nutrients‐depleted with concentrations of nitrate, phosphate, and silicate, 13–18% lower than the rich surrounding waters. However, the nutriclines are shifted of about 20–50 m toward the surface thus increasing the nutrients availability for phytoplankton. Chlorophyll‐a concentrations at the deep chlorophyll maximum are subsequently about twice bigger as compared to outside. Pigments further reveal the predominance of nanophytoplankton inside the eddy and an enhancement of the primary productivity. This study demonstrates the important impact of postconvective SCVs on nutrients distribution and phytoplankton community, as well as on the subsequent primary production and carbon sequestration. Plain Language Summary: Due to harsh meteorological conditions in winter, a few places of the world's ocean experience an intense cooling of their surface waters that start to sink in a process called oceanic deep convection. It is crucial for the functioning of the ocean, but also the marine biology as it brings oxygen deep below the surface and nutrients up to the surface thereby stimulating phytoplankton growth. In this study, we describe with unprecedented details the physics and its biological implications of an eddy formed after a convective event occurring in winter 2013 south of France in the northwestern Mediterranean Sea. This oceanic eddy has a radius of about 6 km and a subsurface signature with intensified rotation of about 15 cm/s at around 750 m. Its size is rather small for an oceanic eddy and makes it particularly challenging to sample and detect. This type of eddies are able to live for years in the quiescent deep ocean and this specimen was observed 4.5 months after its formation. Water samples collected by a ship inside the eddy enable us to further evaluate for the first time its influence on the nutrients concentration, as well as on the phytoplankton size group. Key Points: A submesoscale coherent vortex is characterized using shipborne measurements (CTD and water samples) combined with glider data The eddy is very nonlinear with vorticity reaching −0.8 f and coherent with a diffusive half‐life of about 2.5 year The eddy is nutrient‐depleted at depth, but enhances phytoplankton growth (especially microphytoplankton) as well as primary production